Internet connectivity disruption in India (India) - Voidly (2026)
CRITICAL severity disruption detected in India. Confidence: 75%. Data sourced from IODA.
Network Disruption Incident ID: IN-2026-0053
Keywords: internet disruption; IN; disruption; critical